Megalithic statue (moai) production on Rapa Nui (Easter Island, Chile) - Carl Philipp Lipo; Terry L. Hunt; Gina Pakarati; Thomas Pingel; Noah Simmons; Kevin Heard; Laryssa Shipley; Caroline Keller; Colin Omilanowski (PLoS ONE, 2025)
Ethnohistoric and recent archaeological evidence suggest that Rapa Nui (Easter Island, Chile) was a politically decentralized society organized into small, relatively autonomous kin-based communities across the island. The more than 1,000 monumental statues ( moai ) of Rapa Nui thus raise a critical question: was production at Rano Raraku—the primary moai quarry—centrally controlled or did it mirror the decentralized pattern found elsewhere on the island? Using Structure-from-Motion (SfM) photogrammetry with over 11,000 UAV images, we created the first comprehensive three-dimensional model of the quarry to test these competing hypotheses. Our analysis reveals 30 distinct quarrying foci distributed across the crater, each containing redundant production features and employing varied carving techniques. This spatial organization, combined with evidence for multiple simultaneous workshops constrained by natural boundaries, indicates that moai production followed the same decentralized, clan-based pattern documented for other aspects of Rapa Nui society. These findings challenge assumptions that monumentality requires hierarchical control, instead supporting emerging frameworks that recognize how complex cooperative behaviors can emerge through horizontal social networks. The high-resolution 3D model also establishes a crucial baseline for the cultural heritage management of this UNESCO World Heritage site, while advancing methodological approaches for testing sociopolitical hypotheses through the spatial analysis of archaeological landscapes.